South Africa: Developing an Internationalization Policy - Jooste, Nico; Hagenmeier, Cornelius (International Higher Education, 2021)
South Africa has completed a process of developing a national policy framework for internationalization. Following a transparent public participation process, the policy became legally binding in November 2020. It is expected to provide a broad agenda for internationalization and requires universities to adopt institutional internationalization strategies or policies. The policy provides the sector with clear guidance on internationalization for the post-COVID-19 pandemic period, and could become a model for the developing world.